Seminal plasma proteomics of asymptomatic COVID-19 patients reveals disruption of male reproductive function - Huang, Jialyu; Su, Yufang; Wang, Jiawei; Fang, Zheng; Zhang, Yiwei; Chen, Hong; Wan, Xinxia; Xiong, Yuanhuan; Song, Ning; Chen, Houyang; Wu, Xingwu (BMC genomics, 2025)
Background A considerable proportion of males suffer from asymptomatic SARS-CoV-2 infection, while the effect on reproductive function and underlying pathomechanisms remain unclear. Results The total sperm count decreased evidently after asymptomatic infection, yet all semen samples were tested to be SARS-CoV-2 RNA negative. Through label‑free quantitative proteomic profiling, a total of 733 proteins were further identified in seminal plasma from 11 COVID-19 patients and seven uninfected controls. Of the 37 differentially expressed proteins, 23 were upregulated and 14 were downregulated in the COVID-19 group compared with control. Functional annotations in Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), and Reactome showed that these proteins were highly enriched in infection, inflammation, and immunity-related pathways as well as spermatogenesis-associated biological process. Four proteins were significantly correlated with one or more semen parameters in Spearman’s coefficient analysis, and seven were filtered as potential hub proteins from the interaction network by MCODE and Cytohubba algorithms. Furthermore, we verified the proteomic results by Western blot analysis of three representative proteins (ITLN1, GSTM2, and PSAP) in the validation cohort. Conclusions In summary, our study showed that acute asymptomatic COVID-19 could alter the seminal plasma protein profile without direct testicular infection and consequently lead to impaired semen quality. These novel findings should enlighten the physicians about the adverse effects of SARS-CoV-2 infection on male fertility, and provide valuable resources for reproductive biologists to further decipher the molecular functions.